Bacterial spot and bacterial canker of stone fruit trees : challenges in producing disease-free propagating material - Goodman, C. A.(Christopher Alan) (Stellenbosch : Stellenbosch University, 2012)
Thesis (M. Sc.) -- University of Stellenbosch, 1986.